PERANAN MAJELIS TAKLIM BERBASIS PEMBERDAYAAN MASYARAKAT DI MASJID DALAM MENANGKAL PAHAM RADIKALISME DI KOTA MEDAN - Rahmadi Ali; Al Kausar Saragih; Rofiqoh Hasan Harahap (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to see the role of the Taklim Council in countering radical ideas centered on mosques which have recently been rampant in the city of Medan. The mosque is a house of worship as well as a place for the transmission of knowledge as well as a center for social activities for Muslims, one of the institutions that often uses mosques as a place for transmitting knowledge is the Taklim Council. This type of research is a qualitative research that is descriptive research. The results of this study are: 1. The efforts of the Ministry of Religion of Medan City in fostering the Taklim Council in Medan, include the following: 1) Providing Legal Status, 2) Guiding the Taklim Council by Non-PNS Religious Counselors in the form of: (1) Administrative coaching, ( 2) Religious Development. 2. The pattern of community empowerment managed by the taklim assembly in Medan , including: First, strengthening in the management of the Mosque Welfare Board (BKM). Second, the implementation of the Da'wah of the Muballigh (lecturers) through the determination of lecture material. Third, fundraising from members of the BKM / Taklim Council and the congregation of the mosque in general. Fourth, inventory management in the form of facilities and infrastructure owned by BKM / Taklim Council within the framework of community empowerment. Fifth, consolidation of BKM administrators and mosque congregations. Sixth, strengthening BKM as a formal institution